PENGARUH KINERJA KEUANGAN TERHADAP PROFITABILITAS PT BANK NEGARA INDONESIA (Persero) Tbk - Salsabila. B (STIE Madani Balikpapan, 2025)
This study aims to analyze the effect of CAR (Capital Adequacy Ratio), FAT (Fixed Asset Turnover), and FDR (Financing to Deposit Ratio) on the profitability of PT Bank Negara Indonesia (Persero) Tbk., as measured by Return on Assets (ROA). This research employs a quantitative approach with an associative research type. Secondary data in the form of financial statements of PT Bank Negara Indonesia (Persero) Tbk. for a specific period were analyzed using multiple linear regression techniques. The results show that CAR has a positive but not significant effect on ROA. Both FAT and FDR have a positive and significant effect on ROA. The simultaneous test (F-test) indicates that CAR, FAT, and FDR collectively have a significant effect on ROA. This study concludes that fixed asset efficiency and the effectiveness of credit distribution play an important role in the profitability of PT Bank Negara Indonesia (Persero) Tbk. The bank needs to maintain a balance between both factors and ensure adequate capital to achieve optimal financial performance.